Grid Interconnection of Renewable Energy Sources Using Modified One-Cycle Control Technique - Sunil, NKV.Sai; Kumar, K.Vinod (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Renewable energy sources are gaining importance these days owing to the fact of the ever increasing electric energy demand which could not be met by the non-renewable sources of power generation due to their depletion at a very fast rate. Hence, renewable sources of energy are interconnected with the existing grids to increase the power capability. This paper presents a modified one cycle control technique to control the switches used in the three phase four leg converter used as the interface converter to interconnect the wind energy conversion system(WECS) to the existing grid by which it overcomes the problem faced by the one-cycle control while operating during light load conditions and also helps to minimize the load voltage and current harmonic contents to a very low value. The simulation is carried out using MATLABSIMULINK and the output waveforms are observed.